Peritoneal (Paraovarian) Malignant Mesothelioma - Erna Kristiani; Stephanie Marisca (Fakultas Kedokteran Universitas Pelita Harapan, 2018)
Peritoneal Malignant Mesothelioma (PMM) is uncommon disease, but increasing in frequency nowadays. This highly aggressive malignancy occurs most commonly in older men and has a strong association with asbestos exposure. It manifests most often as diffuse sheet-like or nodular thickening of the peritoneal surfaces, but it may occasionally be a localized mass. The very large variations of its clinical features and its histological appearance mimicking adenocarcinoma make this tumor is difficult to diagnose.We report a case of PMM that previously diagnose as adenocarcinoma of the ovary. A 29 year-old female came to gynecology clinic with para-ovarian mass. She had no history of asbestos exposure. The mass was oval 9x6x6 cm in size, whitish and firm. Microscopic features showed papillary dense structure with desmoplastic stroma, covered by a layer of cuboidal to columnar cells. The cells with mild pleomorphism and hyperchromatic nuclei, mitotic figures were minimal. The immunohistochemistry tests revealed positive for D2-40, Calretinin, CK8 and CK 18, weakly positive for Inhibin and EMA, and negative for CEA and AFP. Patient had been received chemotherapy, there were no metastasis.